Goiás, patrimônio da humanidade: aproveitamento socialmente compartilhado ou exclusão social? - Fraga, Ademar Duarte (2005)
This study aims to consider how insertion’s process of the historic site of the City of Goiás in the World Heritage reference framework, by United Nations Educational, Scientific and Cultural Organization (UNESCO) and, perceived as a symbolic capital of socially shared mode, the historic heritage delimits an area in which its social agents take positions and redefines cultural life and the destiny of this city. The theme’s choice results of our exploratory inquiries about City of Goiás’ daily that indicated the reordering of urban, due this process, updates, in that heritage’s area, the symbolic structures of social and political order dating back to the colonial order. Are unconscious principles, anchored in the old ways of life, which legitimize unequal distribution of social capital inherent in the collective heritage and establish new expressions of power based on traditionalism. The analysis includes the conformation and demarcation of the heritage's area, as well as its relationship with the Ethos of traditionalism and, also, the empirical basis, through interviews and questionnaires applications, such as people's perceptions correlate material and symbolic deprivations with distribution's form of modalities of capital represented by the historic heritage and the very title of World Heritage.